Lone Mothers in Chiang Mai with Experiences of Social Stigma - Wiwatwongwana, Rangsima; Dhedchawanagon, Kittiwin (Community and Social Development Journal, 2022)
This article explains the outcome of the study to strengthen the knowledge of the experience of being lone mothers by focusing on the way “social stigma” and “social support” are involved in the creation of the women's experience in and being alone mothers in contemporary Thai society. In this article, researchers have studied the experiences and views described by the goal. The stories of the lone mothers of 18 people living in Chiang Mai are brought to the dialogue, reflecting the perception and experience of stigma and dealing with that stigma. In this place, researchers have included the “experts” in the future because they are interested to cover a wider group of stigma experiences. So specialists will be able to provide greater experience through the stories that the service provider or lone mothers to receive help in order to answer. The research question, “how much is that the social stigma/discrimination has created an experience of lone mothers in Chiang Mai”. It is a guideline for analyzing data, as well as lone mothers. However, the tools from this theory are not suitable for the stigma of lone mothers. Therefore, the researchers have taken three benefits to this research: 1) stigma experience 2) dealing with stigma and 3) ashamed and self-punishment. In addition, in this article, the story of the stigma lone mothers arranged by looking at the type of lone mothers that found that age group is a similar feature of the type of lone mothers that some of them are associated with the seals at stigma they. While other groups of lone mothers are older, the seals that occur are different.